Influence of the micro-structural factors upon thermal and mechanical properties of various bag leathers - Mondal, AK; Chattopadhyay, PK (Bangladesh Journal of Scientific and Industrial Research, 2017)
Four different bag leathers, such as, Sheep Bag Leather (SBL), Buffalo Vegetable Tanned Leather (BVTL), Cow Drum Dyed Dry Milled Leather (CDDDML), and Cow Crocodile Print Leather (CCPL), were processed by different methods from respective wet-blues of Indian origin. Thermal degradation pro?le and mechanical properties of the samples were evaluated, and crosslink densities of each sample were measured by ?tment of Mooney-Rivlin equation on stress-strain plots. Morphological characteristics (e.g. ?bre structure, ?bre thickness, splitting etc.) of all the specimens were investigated by image analyses of SEM photomicrographs. The highest crosslinking density for BVTL was attributed to its higher ?bre and ?bril thicknesses coupled with rigorous retanning by vegetable tannins and syntans. Embossing at higher temperature and pressure reduced CCPLs elongation-at-break value and hence stretchiness possibly due to the development of set properties within the CCPL matrix. SBL was noted to contain huge void spaces that increased its stretchiness, and melamine formaldehyde syntans showed pronounced in?uence in increasing the thermal resistance of both CCPL and CDDDML. Bangladesh J. Sci. Ind. Res. 52(3), 167-176, 2017